Diurnal and Seasonal Variations of Water Vapour and Cloud Water Attenuation in Microwave Frequency Bands - Fiser, O.; Rezacova, D. (Radioengineering Society, 1997)
20 years of radiosonde data from the aerological station Prague-Libus were analysed to evaluate integrated values of water vapour content and cloud water content. Both parameters are proportional to the attenuation in microwave frequency bands. The soundings from 00, 06, 12, and 18 UTC were taken into account to discuss diurnal as well as seasonal variations. The methods available to compute the cloud and the water vapour attenuation are presented.
Keywords: water vapour content; WVC; cloud water content; CWC; Diurnal and seasonal variations; atmospheric attenuation; radiowave propagation